2007
DOI: 10.2174/156652407781695729
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile Neuronal Ceroid-Lipofuscinosis (Batten Disease): A Brief Review and Update

Abstract: Juvenile neuronal ceroid-lipofuscinosis (JNCL, Batten disease, Spielmeyer-Vogt-Sjogren disease, CLN3) is the most common inherited, autosomal recessive, neurodegenerative disorder in man. Like the other neuronal ceroid-lipofuscinoses, it is characterized by progressive loss of vision, seizures, and loss of cognitive and motor functions, leading to premature demise. JNCL is caused by mutations of CLN3, a gene that encodes a hydrophobic transmembrane protein, which localizes to membrane lipid rafts in lysosomes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 86 publications
0
26
0
Order By: Relevance
“…Defects in lysosomal function may curtail degradation, which can result in the accumulation of substances within the lysosome. Lysosomal storage diseases (LSDs) represent a subgroup of inborn errors of metabolism primarily resulting from a deficiency of one or more lysosomal enzymes involved in macromolecule degradation, (for review see (Schultz et al, 2011, Cox and Cachon-Gonzalez, 2012, Platt et al, 2012, Boustany, 2013), although in some LSDs, the function of mutated protein(s) has yet to be determined (Bruun et al, 1991, Rakheja et al, 2007). Since the discovery of lysosomes by Christian de Duve (De Duve, 1963, 1966), over 60 distinct LSDs have been described, with a collective incidence estimated at 1:5,000 live births world-wide (Fuller et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Defects in lysosomal function may curtail degradation, which can result in the accumulation of substances within the lysosome. Lysosomal storage diseases (LSDs) represent a subgroup of inborn errors of metabolism primarily resulting from a deficiency of one or more lysosomal enzymes involved in macromolecule degradation, (for review see (Schultz et al, 2011, Cox and Cachon-Gonzalez, 2012, Platt et al, 2012, Boustany, 2013), although in some LSDs, the function of mutated protein(s) has yet to be determined (Bruun et al, 1991, Rakheja et al, 2007). Since the discovery of lysosomes by Christian de Duve (De Duve, 1963, 1966), over 60 distinct LSDs have been described, with a collective incidence estimated at 1:5,000 live births world-wide (Fuller et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The CLN3-encoded protein Battenin usually localizes to the endosome and lysosome in mammalian cells. Although the primary function of Battenin is yet unclear, lacking of normal Battenin affects numerous cellular functions including pH regulation, arginine transport, membrane trafficking, and apoptosis [28]. The CLN8 protein, localizes to the endoplasmic reticulum (ER) and the ER to Golgi intermediate com- Lag1) and may impact dihydroceramide synthase.…”
Section: Discussionmentioning
confidence: 99%
“…Although JNCL is the most common of all neuronal ceroid-lipofuscinoses and CLN3 was identified approximately 20 years ago, the highly hydrophobic nature of the CLN3 protein (CLN3P) has precluded its purification and therefore hindered attempts at direct functional studies. While the primary function of CLN3P may be debated, its absence affects numerous cellular functions including pH regulation, arginine transport, organelle or membrane trafficking, and apoptosis [2,20]. We have suggested that the unifying primary function of CLN3P may be in a novel palmitoyl-protein -9 desaturase (PPD) activity, which is present at intermediate levels in heterozygotes.…”
Section: Rakheja and Mj Bennett / Neuronal Ceroid-lipofuscinosesmentioning
confidence: 99%